Enhanced photocatalytic performance of Zr(IV) doped ZnO nanocomposite for the degradation efficiency of different azo dyes - E. Jackcina Stobel Christy (KeAi Communications Co., Ltd., 2021)
Semiconductor photocatalysts have drawn attention towards environmental applications due to their outstanding properties to induce photocatalytic oxidations i.e. complete degradation of contaminants over the surface of the nano-materials under UV light irradiation. In this work, Zr(IV) doped ZnO photocatalyst was fabricated by the sol-gel technique with the different weight ratio of Zr(IV) loadings. In order to examine various influencing parameters viz., solution pH, irradiation time, catalyst dosage, initial concentration of dye molecules, the above studies were performed under UV light irradiations. The as-fabricated Zr(IV) doped ZnO nanocomposite was characterized by XRD, SEM with EDAX, TGA and FTIR techniques. Crystalline size and microstrain of 4% Zr(VI) doped ZnO nanocomposite were found to be 73.76 nm and 0.0634%, respectively. The photodegradation of three azo dyes namely Reactive Red 141 (RR 141), Reactive Yellow 105 (RY 105) and Reactive Orange 84 (RO 84) using 4% Zr(IV) doped ZnO nanocomposite was explored under UV light irradiation. The degradation efficiency of RR 141, RY 105 and RO 84 followed the pseudo-first-order kinetics according to the Langmuir-Hinshelwood model. Furthermore, the degraded products were analyzed using TOC. The reusability of as-prepared Zr(IV) doped ZnO nanocomposite was assessed.